2011
DOI: 10.1039/c0mb00237b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the genecluster involved in muraymycin biosynthesis from Streptomyces sp. NRRL 30471

Abstract: Muraymycin, a potent translocase I inhibitor with clinical potential, is produced by Streptomyces sp. NRRL 30471. The structure of muraymycin is highly unusual and contains the hexahydro-2-imino-4-pyrimidylglycyl moiety (epicapreomycidine) and an ureido bond. Here we report the identification of the muraymycin gene cluster from Streptomyces sp. NRRL 30471. Sequencing analysis of a 43.4-kb contiguous region revealed 33 ORFs, 26 of which were proposed to be involved in muraymycin biosynthesis. Independent target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
(56 reference statements)
2
41
0
1
Order By: Relevance
“…Identification of the Riboflavin Catabolic Gene Cluster-A cosmid library was constructed for the isolation of the riboflavin catabolic gene cluster (17). After failing to identify the gene cluster by screening this library in Escherichia coli, Streptomyces lividans 1326 was chosen as the heterologous host because Microbacterium and Streptomyces both have similar genomic GC content (ϳ70%).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the Riboflavin Catabolic Gene Cluster-A cosmid library was constructed for the isolation of the riboflavin catabolic gene cluster (17). After failing to identify the gene cluster by screening this library in Escherichia coli, Streptomyces lividans 1326 was chosen as the heterologous host because Microbacterium and Streptomyces both have similar genomic GC content (ϳ70%).…”
Section: Resultsmentioning
confidence: 99%
“…To achieve engineered production of 2=-Cl PTN and 2=-amino dA in a heterologous host, a positive cosmid, 3G12, housing the probable complete ada gene cluster, was screened from the genomic library of Actinomadura sp. ATCC 39365 by a narrowdown PCR strategy (16) and introduced into the heterologous host Streptomyces aureochromogenes CXR14 (17). Subsequently, the recombinant strain (CXR14::3G12), confirmed by PCR, was fermented for further metabolic analysis, and the LC-MS results indicated that the targeted [MϩH] ϩ ions of 2=-Cl PTN (m/z 303.0825), PTN (m/z 269.1220), and 2=-amino dA (m/z 267.1175) could be clearly detected from the sample of the CXR14::3G12 recombinant.…”
Section: Resultsmentioning
confidence: 99%
“…2) (29,30). Additional members of the GlyU-containing nucleoside antibiotics with identified biosynthetic gene clusters include liposidomycins (31), caprazamycins (32), muraymycin (33), muraminomicin (34), and the recently discovered sphaerimicins (35). Thus, the uncovering of these two genes within the clusters for 1 and 2 suggested that the biosynthesis of CarU proceeds via condensation of L-Thr with UA to generate GlyU as a cryptic pathway intermediate.…”
Section: Capuramycin-type Antibiotics Include A-500359s Frommentioning
confidence: 99%